Qualitative Study of Topic Mapping in Descriptive Texts by Seventh Grade Students at Colomadu Public Junior High School 3 - Meilawati, Marlina Yuan; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to map the variety of topics in descriptive texts written by seventh-grade students at SMP Negeri 3 Colomadu. Previous studies have not extensively mapped topics in descriptive texts written by junior high school students. This study uses a qualitative descriptive method by analyzing 14 texts. The results show seven topic categories, with animals dominating five texts, followed by places in three texts and food and drinks in two texts, while objects, figures/families, concepts/abstracts, and plants only appeared once. These findings show a tendency for students to choose concrete objects that are close to their daily experiences. This study contributes to the understanding of students' topic selection patterns, which teachers can utilize to develop descriptive writing learning strategies that are more suitable for the characteristics of their students.